Evaluation of the Success Supplementary Feeding Program (PMT) for Toddlers with Undernutrition - Farida Hendriana; Endah Mulyani (Indonesian Journal of Global Health Research, 2024)
Good nutritional status is a determining factor for the success of developing quality human resources. Toddlers are one of the groups vulnerable to nutrition that need special attention. Efforts made to overcome malnutrition in toddlers are by providing additional food (PMT) based on local food ingredients. Objective: This study aims to spark the success of the local food-based additional food program for malnourished toddlers at the Glagah Health Center, Lamongan Regency. The design of this study was experimental with pretest and posttest. The location of the study was in the Glagah Health Center work area, Lamongan. Based on data from the PMT monitoring report, the study population involved 100 toddlers aged 19-60 months with malnutrition status with total based on the weight to height (BB/TB) indicator used in assessing nutritional status. Use total sampling techinc. Statistical tests were carried out using the Paired Sample T-test with a significance value of <0.05. The study showed a significant increase after 56 days of receiving PMT and monitoring was carried out which showed a difference in BB/TB before and after the PMT was given with a p value = 0.000. There is effectiveness in providing additional food based on local food ingredients to toddlers with poor nutritional status in the Glagah Health Center work area, Lamongan.